Development of a Wearable Wireless Sensing Device for Characterization of Hand Tremors Through Vibration Frequency Analysis - Yousef, Mo’ath; Hafizh, Muhammad; Sassi, Sadok; Adeli, Gholam (Journal of Vibration Engineering & Technologies, 2023)
Purpose To monitor the progression of diseases such as Parkinson’s disease (PD) or essential tremor (ET), there is a growing interest in understanding their side effects and continuously monitoring the deterioration or progress of patients’ health conditions. The objective of this study was to investigate the feasibility of a wearable monitoring device constructed from compact MEMS for robust tremor detection in the upper limb using three different storage and monitoring techniques. Method Four subjects (2 PD and 2 ET) with varying stages of disease and treatment willingly provided offline, online, and live modes of tremor data using a low-cost, miniaturized accelerometer and microelectromechanical device. Results The results demonstrated differences in voluntary and non-voluntary characteristics of various activities and the distinct separation between them in the vibration spectrum at the limit of 2 Hz. Online and live monitoring provided the best alternatives to continuous in-home tracking combined with extensive post-processing techniques to detect tremor segments. The findings also highlighted the emergence of noticeable peaks, in the range between 3 and 8 Hz, for the PD’s frequency response, compared to the ET case, where the broadband behavior dominates. Conclusion The possibility of using a dynamic tuned mass damper tuned with dominant peaks to be canceled opens opportunities for PD passive tremor suppression.